Algorithm For Establishing the Financial Profit from Reducing the Mass of the Aircraft: Optim-Based Optimization Approach - Katarzyna KANIA 1; Sylwia PANGSY-KANIA 2; Floros FLOUROS 3 (Communications of International Proceedings, 2025)
In this paper, the algorithm for establishing the financial profit from aircraft’s mass reduction is presented. It is applied to two examples: a passenger and a general aviation aircraft. Comparing them shows that reducing the aircraft’s mass allows for high financial profit for large aircraft, while in general aviation, more revolutionary solutions are needed. Next, the OptiM software is used for determining the distance for which the revenue from taking additional passengers equals alternative financial savings from decreased fuel burn. The optimization methods applied are: Hooke-Jeeves Method, Powell’s method, Steepest Descent Method, Monte Carlo method and genetic algorithms. Among those methods, the Steepest Descent method reaches the exact solution in the least number of iterations, making it the most cost-efficient method. Genetic algorithms, despite their versatility, prove to be less effective for this kind of problem.
Keywords: aerospace engineering; aviation; optimization; economy and finance; algorithm; OptiM software; MATLAB software